Brain alterations in adolescents with first-episode depression who have experienced adverse events: evidence from resting-state functional magnetic resonance imaging - Xia, Xiaodi; Tang, Jinxiang; Peng, Yadong; Liu, Ying; Chen, Yingying; Yuan, Meng; Yu, Renqiang; Hou, Xiao; Fu, Yixiao (Frontiers in Psychiatry, 2024)
Adverse life events constitute primary risk factors for major depressive disorder (MDD), influencing brain function and structure. Adolescents, with their brains undergoing continuous development, are particularly susceptible to enduring impacts of adverse events. We investigated differences and correlations among childhood trauma, negative life events, and alterations of brain function in adolescents with first-episode MDD. The study included 23 patients with MDD and 19 healthy controls, aged 10–19 years. All participants underwent resting-state functional magnetic resonance imaging and were assessed using the Beck Depression Inventory, Childhood Trauma Questionnaire, and Adolescent Self-Rating Life Events Checklist. Compared with healthy controls, participants with first-episode MDD were more likely to have experienced emotional abuse, physical neglect, interpersonal relationship problems, and learning stress (all p’ < 0.05). These adverse life events were significantly correlated with alterations in brain functions (all p < 0.05). This study contributes novel evidence on the underlying process between adverse life events, brain function, and depression, emphasizing the significant neurophysiological impact of environmental factors.